Correlation of liver enzymes with serum ferritin levels in β-thalassemia major - Suman, Rameshwar L.; Sanadhya, Anuradha; Meena, Pradeep; Goyal, Suresh (International Journal of Research in Medical Sciences, 2017)
Background: Liver is the earliest site of iron deposition in transfusion dependent β -thalassemia major and iron induced liver injury is the common cause of morbidity. Liver enzymes are raised and indicative of liver injury in transfusion dependant β-thalassemia major patients. Objective of the study was to find out the correlation of serum ferritin with liver enzymes serum glutamic oxalocetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) in thalassemia major children. Methods: Hospital based study of fifty five (55) children of β-Thalassemia major in the age group of 4-20 years who were regularly transfused and were on oral iron chelators since at least one year were enrolled. Serum ferritin levels and serum SGOT and SGPT levels were estimated and results were correlated. Results: Out of total fifty five (55) children, most were in the age group of 4 to 8 years. Mean rate of blood transfusion in subjects was 157.01ml/kg/year and mean duration of chelation therapy was 2.34 years. Serum ferritin levels were increased in β-thalassemic children with average of 2130.33±859.85ng/ml. The SGOT and SGPT were also raised significantly (p value <0.05) with mean of 71.37±24.16 IU/L and 62.3 5±25.75 IU/L respectively. The values of SGOT & SGPT becomes highly significant (p value <0.001) when serum ferritin becomes more than 2000 ng/ml. Onset of liver enzyme derangement starts at serum ferritin level of more than 1000 ng/ml We found positive correlation between serum ferritin and deranged liver enzymes (Pearson’s bivariate correlation coefficient r = 0.84±84). Conclusions: As soon as the serum ferritin level crosses the value of 1000 ng/ml and number of transfusions are more than 30, derangement in liver enzymes starts occurring in β -thalassemia major.